The Yfe and Feo Transporters Are Involved in Microaerobic Growth and Virulence of Yersinia pestis in Bubonic Plague - Fetherston, Jacqueline D. (American Society for Microbiology, 2012)
The Yfe/Sit and Feo transport systems are important for the growth of a variety of bacteria. In Yersinia pestis, single mutations in either yfe or feo result in reduced growth under static (limited aeration), iron-chelated conditions, while a yfe feo double mutant has a more severe growth defect. These growth defects were not observed when bacteria were grown under aerobic conditions or in strains capable of producing the siderophore yersiniabactin (Ybt) and the putative ferrous transporter FetMP. Both fetP and a downstream locus (flp for fet linked phenotype) were required for growth of a yfe feo ybt mutant under static, iron-limiting conditions. An feoB mutation alone had no effect on the virulence of Y. pestis in either bubonic or pneumonic plague models. An feo yfe double mutant was still fully virulent in a pneumonic plague model but had an ∼90-fold increase in the 50% lethal dose (LD(50)) relative to the Yfe(+) Feo(+) parent strain in a bubonic plague model. Thus, Yfe and Feo, in addition to Ybt, play an important role in the progression of bubonic plague. Finally, we examined the factors affecting the expression of the feo operon in Y. pestis. Under static growth conditions, the Y. pestis feo::lacZ fusion was repressed by iron in a Fur-dependent manner but not in cells grown aerobically. Mutations in feoC, fnr, arcA, oxyR, or rstAB had no significant effect on transcription of the Y. pestis feo promoter. Thus, the factor(s) that prevents repression by Fur under aerobic growth conditions remains to be identified.